Developing and assessing a tool to measure motivation among physicians in Lahore, Pakistan - Malik, Ahmad Azam; Yamamoto, Shelby; Haque, Md. Aminul; Butt, Nadeem Shafique; Baig, Mukhtiar; Sauerborn, Rainer (PLOS ONE, 2018)
Physicians’ motivation plays a vital role in health systems particularly in dense and urban cities, which deal with high volumes of patients in a variety of settings. The loss of physicians due to low motivation to developed countries is also a critical aspect affecting the quality of care in many regions. Fewer studies have explored health provider and particularly physicians’ motivation in developing countries, which is critical to health service delivery. In addition, limited relevant tools have been developed and tested in low and middle-income settings like Pakistan. The purpose of this study was to create and test a tool for measuring physician motivation. A tool was developed to explore physicians’ motivation in the Lahore district, Pakistan. Three sections of the questionnaire, which included intrinsic, socio-cultural and organizational factors, were tested with a stratified, random sample of 360 physicians from the public and private health facilities. Factor analysis produced six factors for ‘intrinsic motivation,’ seven for ‘organizational motivation’ and three for ‘socio-cultural motivation’ that explained 47.7%, 52.6% and 40.6% of the total variance, respectively. Bartlett’s test of sphericity and the KMO were significant. Cronbach's α and confirmatory factor analysis were found satisfactory for all three sections of questionnaires. In addition to identifying important intrinsic, socio-cultural and organizational factors study found the questionnaires reliable and valid and recommend further testing the applicability of the instrument in similar and diverse settings.